Moringa ? the miracle tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Promotion of Moringa oleifera, a plant with numerous medicinal and nutritional benefits which can also purify water.